Fly ash effect on hatching, mortality and penetration of root-knot nematode (Meloidogyne incognita) in pumpkin roots - Ahmad, Gufran; Khan, Abrar Ahmad (International Journal of Environment, 2016)
An experiment was conducted to observe the effect of fly ash on hatching, mortality and penetration of root-knot nematode (Meloidogyne incognita) in pumpkin roots. For hatching experiment different fly ash-extract concentrations (5, 10, 20, 30, 40, and 50%) were prepared. Hatching was significantly reduced in all concentrations, maximum being at 50% concentration. The mortality (%) of juveniles was observed in 1, 2, 3, 4, 5, 6 and 7th days with different levels (5, 10, 20, 30, 40 and 50 %) of fly ash-extract. All the levels were found harmful to juveniles. As the level was increased, the killing percentage of juveniles was also increased. Highest mortality was observed in 7th day with 50% level. For the penetration experiment, fly ash was mixed with soil to prepare different concentrations (5, 10, 20, 30, 40, and 50%). Seeds of pumpkin were grown in coffee cups filled with different mixtures. At two leaf stage, seedlings were inoculated with 2000 larvae. The penetrated larvae in roots were observed after 1, 2, 3, 4, 5, 6 and 7 days. Root penetration was found inversely proportional to concentration. Significant results in the suppression of nematode penetration were noted up to 40% concentration. However, none of the juveniles was penetrated at 50% concentration. International Journal of Environment Vol.5(3) 2016, pp.66-73